Equivalence of Lauric Acid and Glycerol Monolaurate as Inhibitors of Signal Transduction in Staphylococcus aureus - Ruzin, Alexey (American Society for Microbiology, 2000)
Glycerol monolaurate (GML) inhibits the expression of virulence factors in Staphylococus aureus and the induction of vancomycin resistance in Enterococcus faecalis, presumably by blocking signal transduction. Although GML is rapidly hydrolyzed by bacteria, one of the products, lauric acid, has identical inhibitory activity and is metabolized much more slowly. At least four distinct GML-hydrolyzing activities are identified in S. aureus: the secreted Geh lipase, residual supernatant activity in a geh-null mutant strain, a novel membrane-bound esterase, and a cytoplasmic activity.